2015
DOI: 10.3920/bm2014.0070
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum subsp. infantis BB-02 attenuates acute murine experimental model of inflammatory bowel disease

Abstract: Inflammatory bowel diseases (IBD) are chronic inflammatory conditions, characterised by remissions and relapses episodes, whose main manifestations are ulcerative colitis and Crohn's disease. Ulcerative colitis (UC), one of the main forms of IBD, has as standard treatment the use of corticosteroids and anti-inflammatory drugs. The use of antibiotics has been also reported, but the possible adverse effects, such as disturbance of the indigenous microbiota or resistance induction, should be taken into considerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…The extent of neutrophil accumulation in the jejunum tissue was measured by assaying MPO activity, as described below (Elian et al, 2015). Portions of the jejunum were removed and snap frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of neutrophil accumulation in the jejunum tissue was measured by assaying MPO activity, as described below (Elian et al, 2015). Portions of the jejunum were removed and snap frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Cytokine levels were measured according to Elian et al (2015). This is briefly described as follows.…”
Section: Methodsmentioning
confidence: 99%
“…DAI assessment was carried out according to the classical scoring system as described previously (Elian et al, 2015). DAI was the cumulative scores (0-10) from the following three different parameters: faeces consistency (0, normal; 1, soft but still formed; 2, very soft; 3, diarrhoea), presence of blood in faeces (0, negative haemoccult; 1, positive haemoccult; 2, blood traces visible in faeces; 3, rectal bleeding) and weight loss (0, negative weight loss; 1, loss of 1-5 % of body weight; 2, 5-10 % body weight loss; 3, 10-20 % body weight loss; 4, w20 % body weight loss).…”
Section: Methodsmentioning
confidence: 99%
“…Another small study revealed that acute diverticulitis was associated with the overrepresentation of Bifidobacteria, namely Bifidobacterium longum [45]. This finding confirms the presence of a deep disruption of the mucosa-associated microbial communities, even though Bifidobacterium longum has been associated with anti-inflammatory properties for animal models of colitis [46] and human enterocytes [47]. Thus, the bifidobacterial expansion might be interpreted as a homeostatic mechanism, but should be confirmed in larger studies with a comprehensive profiling of the mucosal microbiota.…”
Section: Studies On the Mucosa-associated Microbiotamentioning
confidence: 84%